Tinjauan Isolated Parking Area Terhadap Pelayanan Lalu Lintas Udara di Bandar Udara Internasional I Gusti Ngurah Rai Bali - Nur, Muhammad; Yulia Tristin, Lia; Filky Rihwanul Ayub, Muh (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
I Gusti Ngurah Rai International Airport is one of the present international airports that serves the domestic and international routes, the number of aircraft movements increasingly crowded. The provision of air traffic services scouting maximum, other than specified by the relevant human resources is also a factor of equipment, procedures, and facilities that support the airport. Isolated layout Parking Area located in the taxiway N7P give effect less effective against the smoothness of air traffic services at the I Gusti Ngurah Rai Bali International Airport. Mentioned in Doc 8973 of the Security Manual for Safeguarding Civil Aviation Against Acts of Unlawful Interference, that in case of aircraft hijacking threat, then the aircraft should be directed to isolated parking area. If the area is traversed by a taxiway or runway, then the taxiway and runway should be closed. The purpose of this study was to review the location of the isolated parking area for air traffic service at international airport I Gusti Ngurah Rai Bali.